Modified nanofat grafting: Stromal vascular fraction simple and efficient mechanical isolation technique and perspectives in clinical recellularization applications - Girard, Paul; Dulong, Joelle; Duisit, Jerome; Mocquard, Camille; Le Gallou, Simon; Chaput, Benoit; Lupon, Elise; Watier, Eric; Varin, Audrey; Tarte, Karin; Bertheuil, Nicolas (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The Nanofat Grafting (NG) is a simple and cost-effective method of lipoaspirates with inter-syringes passages, to produce stromal vascular fraction (SVF) and isolate adipose-derived stem cells (ASC). This represents a tremendous interest for the future clinical needs of tissue engineering. In this study we optimized NG technique to increase the yield of ASCs extractions. Methods: We analyzed 3 groups of SVF obtained by 20, 30 and 40 inter-syringe passages. The control group was a SVF obtained by enzymatic digestion with Celase. We studied their cell composition by flow cytometry, observed their architecture by confocal microscopy and observed immunomodulatory properties of the ASCs from each of the SVFs by measuring inflammatory markers of macrophages obtained by an ASC monocyte co-culture. Results: We have established the first cell mapping of the stromal vascular fraction of adipose tissue. The results showed that SVF obtained by 20 inter-syringes passages contains, statistically significantly more total cells, more cells expressing the ASC phenotype, more endothelial cells and produces more CFU-F than the SVF obtained by 30 and 40 passages and by enzymatic digestion. Confocal microscopy showed the presence of residual adipocytes in SVF obtained by inter-syringes passages but not by enzymatic digestion. The functional study indicating an orientation towards a more anti-inflammatory profile and a homogenization of their immunomodulatory properties. Conclusion: This study places mechanically dissociated SVF in the center of approaches to easily extract ASCs and a wide variety and number of other progenitor cells, immediately available in a clinical setting to provide both the amount and quality of cells required for decellularized tissues.